Disparities in colorectal cancer screening among breast and prostate cancer survivors. (5th February 2021) - Dash, Chiranjeev; Lu, Jiachen; Parikh, Vicky; Wathen, Stacey; Shah, Samay; Shah Chaudhari, Ruchi; Adams‐Campbell, Lucile
ABSTRACT: Background: Colorectal cancer (CRC) screening is recommended as an integral part of cancer survivorship care. We compared the rates of CRC screening among breast and prostate cancer survivors by primary cancer type, patient, and geographic characteristics in a community‐based health‐care system with a mix of large and small metro urban areas. Materials and Methods: Data for this retrospective study were abstracted from medical records of a multi‐specialty practice serving about 250, 000 individuals in southern Maryland. Breast (N = 1056) and prostate (N = 891) cancer patients diagnosed prior to 2015 were followed up till June 2018. Screening colonoscopy within the last 10 years was considered to be guideline concordant. Multivariate logistic regression was used to determine the prevalence odds ratios of being concordant on CRC screening by age, gender, race, metro area type, obesity, diabetes, and hypertension. Results: Overall 51% of survivors had undergone a screening colonoscopy. However, there was a difference in CRC screening rate between prostate (54%) and breast (44%) cancer survivors. Older age (≥65 years), being a breast cancer survivor compared to prostate cancer, and living in a large compared to small metropolitan area were associated with a lower probability of receiving CRC screening. Having hypertension was associated with higher likelihood of being current on colonoscopy screening guidelines among survivors; but diabetes and obesity were not associated with CRC screening. Conclusions: Low levels of CRC screening utilization were found among breast and prostate cancer survivors in a single center in Southern Maryland. Gender, comorbidities, and residential factors were associated with receipt of CRC screening. Abstract : Colorectal cancer screening is recommended as part of survivorship care among breast and prostate cancer survivors. We examined the disparities in receipt of colonoscopy screening among breast and prostate cancer survivors in a community‐based health‐care system. Overall, we found low rates of colorectal cancer screening among survivors (51%). Older survivors, breast cancer as compared to prostate cancer survivors, and those living in large compared to smaller metropolitan areas were less likely to have received colonoscopy screening.